2022
DOI: 10.1371/journal.pone.0273286
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and healthcare professionals’ perspectives on a community-based intervention for schizophrenia in Pakistan: A focus group study

Abstract: Objective To explore the perceptions and experiences of schizophrenia from patients, their care givers, health care providers, spiritual and traditional healers to develop a community-based intervention for improving treatment adherence for people with schizophrenia in Pakistan. Methods This qualitative study involved four focus group discussions (FGD) with a total of 26 participants: patients and carers (n = 5), primary care staff (n = 7), medical technicians (n = 8) and traditional and spiritual healers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…8 This is consistent with a systematic review showing predominantly supernatural explanatory models of illness for psychosis in LMICs. 9 Research with TSHs in Pakistan [10][11][12] has identified that the following terms are used for identifying people suffering from psychosis: influence of jinn, saya (influence or shadow), 'strong spell or under the control of spirits' lewanay (insane) and 'superstitious'. This is consistent with previous literature.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…8 This is consistent with a systematic review showing predominantly supernatural explanatory models of illness for psychosis in LMICs. 9 Research with TSHs in Pakistan [10][11][12] has identified that the following terms are used for identifying people suffering from psychosis: influence of jinn, saya (influence or shadow), 'strong spell or under the control of spirits' lewanay (insane) and 'superstitious'. This is consistent with previous literature.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The Open access information gained from ethnographic and qualitative studies will inform the contents, format and methodology for training TSHs. Based on our experience of working with traditional healers in the STOPS+ Programme, 10 the training will mainly focus on the following topics: overcoming barriers to working with psychiatric services, symptoms and signs of FEP and differentiating these from normal behaviours expected in adolescence, attitudes and behaviours towards people with psychosis, avoiding harmful practices, respecting individual autonomy, preventing gender-based discrimination and information about referral pathways.…”
Section: Training For Tshsmentioning
confidence: 99%
“…In this case, lack of access to mental health services is an important issue. In addition, Schizophrenia tends to seek treatment than the general population [4]- [7].…”
Section: Introductionmentioning
confidence: 99%